2019
DOI: 10.1002/1873-3468.13328
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor suppresses gene expression of Rev‐erbα (Nr1d1) through interaction with the CLOCK complex

Abstract: Glucocorticoids have various medical uses but are accompanied by side effects. The glucocorticoid receptor (GR) has been reported to regulate the clock genes, but the underlying mechanisms are incompletely understood. In this study, we focused on the suppressive effect of the GR on the expression of Rev‐erbα (Nr1d1), an important component of the clock regulatory circuits. Here we show that the GR suppresses Rev‐erbα expression via the formation of a complex with CLOCK and BMAL1, which binds to the E‐boxes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Nader et al showed that the transcription factor clock, a master regulator of circadian rhythm, acetylates GR and represses the transcriptional activity of several glucocorticoid-responsive genes [107]. GR also suppresses the expression of Rev-erbα (Nr1d1), which is also an important component of circadian regulation [108]. These findings provide new insights into the role of GR in the regulation of the circadian rhythm.…”
Section: The Role Of Gr In Physiological Conditionsmentioning
confidence: 99%
“…Nader et al showed that the transcription factor clock, a master regulator of circadian rhythm, acetylates GR and represses the transcriptional activity of several glucocorticoid-responsive genes [107]. GR also suppresses the expression of Rev-erbα (Nr1d1), which is also an important component of circadian regulation [108]. These findings provide new insights into the role of GR in the regulation of the circadian rhythm.…”
Section: The Role Of Gr In Physiological Conditionsmentioning
confidence: 99%
“…Interestingly, glucocorticoidinduced phase-shifting did not occur in PER1 knockout models. This suggests that Per plays a major role in mediating the effects of glucocorticoids on other circadian components of the clock mechanism, such as Bmal1, Rev-Erb, and Clock (Koyanagi et al 2006), even though glucocorticoids can directly repress REV-ERB expression (Murayama et al 2019) and CLOCK and CRY have been shown to physically interact with the GR, inhibiting its transcriptional activity (Nader et al 2009, Lamia et al 2011 (Fig. 3).…”
Section: Is the Glucocorticoid Effector System The Watchmaker?mentioning
confidence: 99%
“…Besides heterodimerization on DNA, GR has been suggested to form other protein-protein interactions on chromatin which tether GR to enhancers independently of its DBD. This includes interaction with COUP-TFII, STAT5, PPARα and the molecular clock components BMAL1, CLOCK, and REV-ERBα, influencing GR activity and hepatic metabolism ( 82 , 106 , 115 , 116 , 119 ). For example, COUP-TFII protein interaction with GR is important for GC-induced promoter activity and hepatic Pck1 gene expression ( 106 ).…”
Section: Gr Operates In Transcriptional Network To Control Hepatic Gmentioning
confidence: 99%
“…Also, GR is suggested to be recruited to a subset of sites via tethering to DNA-bound PPARα to regulate metabolic genes in the liver including Pdk4 ( 114 ). Moreover, GR tethering to the BMAL1-CLOCK complex is suggested to repress hepatic Rev-erb α expression ( 115 ), demonstrating how GR and the molecular circadian clock interconnect to regulate shared gene programs.…”
Section: Gr Operates In Transcriptional Network To Control Hepatic Gmentioning
confidence: 99%
See 1 more Smart Citation